Research on Agenda Setting and Public Opinion Guidance of Social Security Events in the New Media Environment (Microblog): Take "Juvenile Delinquency" as an Example - Li, Qiong (International Journal of Social Sciences and Public Administration, 2024)
Whether the issue setting of the media is correct or not plays a positive role in social construction. In the social security incidents in recent years, the withdrawal of cases due to the young age of the offenders has become a topic of intense discussion among the masses. This research intends to employ the content analysis method, in combination with the agenda-setting theory, to explore under this background how major new media platforms should correctly set issues, and evoke social attention and emphasis on such incidents. In the descriptions of these incidents, the emotional color is extremely intense, encompassing various emotions such as anger, disappointment, and regret. Driven by the dissemination of information, the correct setting of issues has indeed pushed all sectors of society to pay attention to such incidents and start calling on the government and legislative institutions to conduct a comprehensive review and significant reform of the relevant laws on juvenile delinquency. These calls not only come from the public but also from the families of the victims and various organizations from all walks of life, which is conducive to promoting social transformation and legal improvement through the guidance of public opinion, thereby achieving positive purposes.